CaMKIIα neurons in the anterior insular cortex regulate attention behavior in mice - Ma, Yingping; Jiang, Shaofei; Zhao, Xin; Li, Shen; Chen, Liping; Zhao, Zhe; Shen, Wei; Wu, Yan; Wu, Haitao (Frontiers in Neural Circuits, 2023)
The insular cortex is involved in multiple physiological processes including working memory, pain, emotion and interoceptive functions. Previous studies have indicated that the anterior insular cortex (aIC) also mediates interoceptive attention in humans. However, the exact cellular and physiological function of the aIC in the regulation of this process is still elusive. In this study, using the 5-choice serial reaction time task (5-CSRTT) testing paradigm, we assessed the role of the aIC in visuospatial attention and impulsiveness in mice. The results showed a dramatic activation of c-Fos in the aIC CaMKIIα neurons after the 5-CSRTT procedure. In vivo fiber photometry revealed enhanced calcium signaling in aIC CaMKIIα neurons when the mice responded correctly. In addition, chemogenetic suppression of aIC CaMKIIα neurons led to increased incorrect responses within the appropriate time. Importantly, pharmacological activation of aIC CaMKIIα neurons enhanced their performance in the 5-CSRTT test. These results provide compelling evidence that aIC CaMKIIα neurons are essential for the modulation of attentional processing in mice.